Komite Audit Memoderasi Debt Covenant dan Related Party Transaction terhadap Keputusan Perencanaan Pajak - Adhitya Putri Pratiwi (Universitas Pamulang, 2020)
This study aims to see empirically the role of the audit committee in moderating the effect of debt covenant and transfer related parties on tax planning decisions. This type of research is quantitative research. This study uses 57 populations of consumption sector companies. The sample in this study was selected using the purposive sampling method and obtained 17 companies that meet the criteria set by the author. The data that has been collected is then processed using the e-views 10 tools. This research shows the result that debt covenant and related party transaction has an effect on tax planning decisions. Meanwhile, the Moderation Regression Test show the results that the audit committee is unable to moderate debt covenant on tax planning decision and the audit committee moderated the effect of related party transaction on tax planning decisions. Keywords: Debt Covenant; Tax Planning Decisions; Transfer Related Party